2022
DOI: 10.1002/ird.2703
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative growth, yield, and water productivity of an early maturing peach cultivar under deficit irrigation strategies in a warm and arid area

Abstract: Deficit irrigation strategies are considered as promising irrigation management for water saving. In the arid areas of southern Tunisia, agriculture relies heavily on irrigation. With rainfall scarcity, valuable management of water requires efficient approaches. In this context, the effects of deficit irrigation (CDI) and partial root zone drying (PRD) on the vegetative and fruiting behaviour of an early maturing peach (Prunus persica cv. Flordastar) were investigated. Shoot and trunk growth, yield, and fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Reduced water availability has a substantial impact on fruit quality, influencing the size, quality, juice yield and flavor of fruit [22,27,28,78]. However, reduced irrigation did not significantly affect walnut morphology and weight in our study (Figure 6), which is consistent with similar research on lemon trees [79].…”
Section: The Influence Of Drought On Nonstructural Carbohydrate Varia...supporting
confidence: 91%
See 1 more Smart Citation
“…Reduced water availability has a substantial impact on fruit quality, influencing the size, quality, juice yield and flavor of fruit [22,27,28,78]. However, reduced irrigation did not significantly affect walnut morphology and weight in our study (Figure 6), which is consistent with similar research on lemon trees [79].…”
Section: The Influence Of Drought On Nonstructural Carbohydrate Varia...supporting
confidence: 91%
“…Irrigation deficits combined with climate change-induced shifts in temperature, rainfall and other climatic factors drastically reduce the performance of many horticultural crops [24,25]. Tree photosynthesis is very sensitive to water deficit [26,27], which directly affects fruit development and final yield [13,28]. To reduce water loss during periods of drought, plants often first down-regulate stomatal conductance (gs) and then may increase osmotic adjustments to facilitate water absorption in drier soils [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Shikimic acid concentration (quinic and citric acids) has been shown to decrease with leaf/fruit ratio increase, while greater assimilate supply is related to high malate [53]. In accordance, our previous study showed that Flordastar trees subjected to DI and PRD 50 have a high leaf/fruit ratio [54]. Additionally, potassium has a key role at a cellular level, whereby different mechanisms allow K + to affect the metabolism and the storage of organic acids.…”
Section: Discussionsupporting
confidence: 79%
“…Huang et al [46] found that the average runoff from cultivated fallow land was very high, reaching 10.3% of the seasonal rainfall, and the evapotranspiration of two kinds of forest and one kind of shrub was 5.2%, 6.6%, and 8.4% higher than that of natural grassland. Water-wise agricultural irrigation and irrigation water efficiency should be encouraged to reduce the demand for water supply services [48,49]. Gao et al [48] found that the practice of 20% deficit irrigation, furrow irrigation, and mulching results in no reduction yield and a relatively low water footprint, which can save up to 20% of irrigation water and 8-12% of effective precipitation in an irrigation district, which is the optimal balance point between the yield and water consumption of the two crops.…”
Section: Suggestions For the Rational Utilization Of Water Resources ...mentioning
confidence: 99%